Analysis of water quality distributed in the city of Altamira-PA (Research, Society and Development, 2022)
Objective: this research aimed to analyze and compare whether standards of potability of water distributed by the Sanitation Coordination of Altamira (COSALT) in residences, in different districts of Altamira, are in accordance with the parameters established by the current regulations. Method: field research, from the collection of water samples in COSALT and in 06 neighborhoods, determined from the analysis of those that had the highest incidence of acute diarrheal cases in May 2022. The physical potability patterns were verified-chemical (turbidity and free residual chlorine) and microbiological (total coliforms and Escherichia coli). Results: the physical-chemical and microbiological analyzes of all samples collected in the present study were in accordance with the parameters required by Ordinance No. 888/21 of the Ministry of Health, which determines the potability values of water for human consumption. Conclusion: The accomplishment of this work demonstrates the importance of perpetuating similar studies, in order to contribute to the monitoring and notification of changes in the quality indices of water for consumption.